Hydrologic and Edaphic Controls on Soil Carbon Emission in Dongting Lake Floodplain, China. Issue 9 (28th September 2018) - Deng, Zhengmiao; Li, Youzhi; Xie, Yonghong; Peng, Changhui; Chen, Xinsheng; Li, Feng; Ren, Yijie; Pan, Baihan; Zhang, Chengyi
Abstract: Wetlands play a critical role in mitigating carbon emission. However, little is known about soil carbon emission and their environmental controls from inland floodplain wetlands. This study aimed to determine the effects of hydrologic and edaphic controllers (water table depth [ WTD ], soil temperature [ Ts ], and soil water content [ SWC ]) on soil C emission in Dongting Lake wetland, China. One‐year emissions were measured in Carex meadow and mudflat using static chambers during 2013 to 2014, including nonflooded season ( NFs ) and flooded season ( Fs ). The results showed that soil C emission in the Carex meadow and mudflat was 307.8 and 264.3 g C·m −2 ·year −1, respectively, and 50–66% of soil C were emitted during NFs. Compared with NFs, CO2 emission was significantly decreased by 57% but CH4 emission was significantly increased by 38 times during Fs in the Carex meadow. Stepwise regression combined with structural equation model analysis showed that CO2 and CH4 flux were mainly influenced by Ts during NFs, and they were controlled by water temperature ( Tw ) during Fs. During NFs, CO2 flux increased with increasing Ts and SWC but decreased significantly when SWC was over 66% and 52% in the Carex meadow and mudflat, respectively. CH4 flux showed an emission pulse at SWC and Ts of 65% and 17.2 °C, respectively. These results indicate that flooding significantly inhibited soil CO2 emission but stimulated CH4 emission. The continuous decrease of flooding days caused by anthropogenic disturbances may induce soil C loss in Dongting Lake wetlands. Key Points: Soil C emission in Dongting Lake floodplain was 264.3–307.8 g C.m ‐2 .year ‐1 Flooding significantly inhibited soil CO2 emission but stimulated CH4 emission The decline of flooding days in Dongting Lake wetlands can potentially increase soil C loss